One Piece Anime As Popular Culture (Study On Millenials In Bengkulu City) - Geronimo, Ronalds Anjrelia; Sari , Sapta; Yanto, Yanto (Multidisciplinary Journals, 2024)
This study aims to find out One Piece Anime so that it becomes popular culture among millennials in Bengkulu city. This study used communication theory, anime theory, cultural theory, popular culture theory, and millennial theory. This study also used qualitative research methods. Data collection techniques in this study using the method of observation, interviews, documentation. In general, the results of the study conclude that how One Piece Anime becomes Popular Culture among Millennials in Bengkulu City which has been going very well. Based on the reciprocity of communication flows and cultural trends that arise in society created by One Piece anime fans which can exchange information and spread the culture. Thus, it makes people can accept the existence of this culture. Many people also follow cultural trends, for example imitating styles like characters in anime. For example, Monkey D Luffy who has a spirited character that doesn't complain, always fights to the maximum, makes friends with any race. This character can be applied in everyday life and affects the social community. Likewise with fashion, such as clothes, hairstyles and accessories, for example the shirt that Luffy wore in the Deseirosa Arc.